Evaluation of Plant Extracts against Stemphylium Blight of Lentil - Subedi, S.; Shrestha, S. M.; KC, G. B.; Thapa, R. B.; Ghimire, S. K.; Gharti, D. B.; Neupane, S. (Nepal Journal of Science and Technology, 2016)
Experiments were carried out to evaluate five different plant extracts against lentil stemphylium blight (Stemphylium botryosum Walr.) at the Grain Legume Research Program, Rampur, Chitwan, Nepal during two winter seasons (2011/ 12 and 2012/13) using CRD in laboratory and RCBD in field conditions. Water extract of Acorus calamus at higher dose (8% W/V) was able to check the growth of the pathogen completely in-vitro. The mycelial growth inhibition (%) of Xanthoxylum armatum and Lantana camera at 8% concentration in PDA were 31.17 and 24.56 respectively. In the field experiment during 2011/12, extracts were sparingly effective for a short period. However the disease control (PDC) was higher in X. armatum treated plot (31.60%) followed by A. calamaus (28.69%) and L. camera (27.61%) when compared to unsprayed plot. The following year (2012/13) field experimental results also verified the effect of plant extracts against the disease. The lower Disease (%) Index (PDI) was obtained from the plots treated with A. calamus (35.33%) and X. armatum (35.55%). Higher crop yield was recorded from the plot treated with A. calamus (987.39 kg/ha) followed by X. armatum (972.78 kg/ha). Two years’ experimental results revealed that A. calamus and X. armatum were effective botanicals to manage lentil Stemphylium blight. Nepal Journal of Science and Technology Vol. 16, No.1 (2015) pp. 11-16